2009
DOI: 10.1007/s10833-008-9101-y
|View full text |Cite
|
Sign up to set email alerts
|

Turning around failing organizations: Insights for educational leaders

Abstract: Purpose In this article, we review the literature from the organizational sciences to develop a grounded narrative of turnaround in education. Approach The approach is a review of literature. We employ an integrated process to unpack and make sense of the turnaround literature from the organizational sciences. We rely on strategies appropriate for document analysis, and borrow analytic strategies (e.g., memoing, coding) employed with interview data. Findings We examine seven defining themes that flow from our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 55 publications
(61 reference statements)
1
21
0
Order By: Relevance
“…In fact, Marks and Printy [36] found that the response to state accountability policies in Ohio undermined organizational learning capacity in schools by reducing participative decision making, collaborative activity, and the transfer of knowledge and skills. Similarly, two recent reviews of the organizational sciences literature [37,38] note the critical aspect of school leadership in successful turnaround systems.…”
Section: Factors Supporting Organizational Learningmentioning
confidence: 99%
“…In fact, Marks and Printy [36] found that the response to state accountability policies in Ohio undermined organizational learning capacity in schools by reducing participative decision making, collaborative activity, and the transfer of knowledge and skills. Similarly, two recent reviews of the organizational sciences literature [37,38] note the critical aspect of school leadership in successful turnaround systems.…”
Section: Factors Supporting Organizational Learningmentioning
confidence: 99%
“…In the literature, terms such as “school improvement” or “school reform” often refer to incremental improvement over long periods of time (Herman et al, 2008). The term “turnaround,” however, has been more distinctly defined as improvement that is quick and dramatic (Duke, 2012) and marked by drastic disruption (Meyers & Smylie, 2017) and a sense of urgency (Murphy, 2010). Although large-scale reviews of turnaround literature indicate varied measures of what constitutes “turnaround” in education (Hochbein, 2012; Meyers & Hambrick Hitt, 2017), the term most often refers to rapid improvement in student outcomes, specifically increases in standardized test scores (Herman et al, 2008; Meyers & Hambrick Hitt, 2017; Peck & Reitzug, 2014).…”
Section: Teaching Notesmentioning
confidence: 99%
“…There are few empirical studies of turnaround as related specifically to education. Much of the current research consists of qualitative studies and interviews (Meyers & Hambrick Hitt, 2017) or is borrowed from organizational and business literature (Murphy, 2010). However, review of the existing research does indicate some common features of successful turnarounds.…”
Section: Teaching Notesmentioning
confidence: 99%
“…Building leadership capacity is crucial to the sustainability of organisational change (Murphy, 2010), within the Solomon Islands context, but this goes hand in hand with respect for, and inclusion of, indigenous cultural considerations.…”
Section: Leadershipmentioning
confidence: 99%
“…At the start of the Partnership, the SOE programmes were out of date, facilities and resources very poor, staff morale low and there was a lack of strategic planning (NZAID, 2006). The SOE could thus be described as a failing organisation (Murphy, 2010). This is commonplace in fragile states, where "… these concepts [fragile states and fragility] incorporate ideas that underline a government's weak capacity to provide social services such as education" (Mosselson, Wheaton, & St. John Frisoli, 2009).…”
Section: Introductionmentioning
confidence: 99%